The Influence of Digital Financial Literacy, Self Control, and Financial Behavior on the Consumptive Behavior of Gen Z QRIS Users in Medan City - Fahkraini Amelia; Pipit Buana Sari; Geby Citra Ananda (Universitas Dehasen Bengkulu, 2026)
This study aims to examine the effect of digital financial literacy, self control, and financial behavior on the consumptive behavior of Generation Z QRIS users in Medan City. It uses a qiantitative approach with an online questionnaire survey method. The number of respondents in this study was 100 people, determined using a sampling technique. Data analysis was conducted using multiple linear resgression with the help of SPSS software. The results of the study indicate that digital financial literacy, self control, and financial behavior partially have a significant negative effect on consumptive behavior. The three variables also show a simultaneous effect on consumptive behavior. These findings confirm that improving digital financial literacy, self control, and good financial behavior play an important role in reducing the consumptive behavior of Generation Z QRIS users.